KONSELING INDIVIDUAL UNTUK MENINGKATKAN KEDISIPLINAN SISWA DI SEKOLAH DENGAN CARA PENDEKATAN BEHAVIOUR REALITA DI SMP PGRI 3 BANJARMASIN - Nur Latifah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2017)
The purpose of this study was to determine kedisplinan eighth grade students at SMP PGRI 3 Banjarmasin before and after behavior techniques reality in individual counseling services program, as well as to determine the effectiveness of counseling techniques in improving discipline in class VIII SMP PGRI 3 Banjarmasin. This research is a quantitative method of experiment, the research was conducted in SMP PGRI 3 Banjarmasin. The population in this study were students in class VIII, amounting to 22 people. The research sample is obtained by using purposive sampling technique which consists of 4 people. The research instrument used was peralukan material in the form of